Biventricular dyssynchrony on cardiac magnetic resonance imaging and its correlation with myocardial deformation, ventricular function and objective exercise capacity in patients with repaired tetralogy of Fallot. (1st August 2018) - Kalaitzidis, Pantelis; Orwat, Stefan; Kempny, Aleksander; Robert, Radke; Peters, Brigitte; Sarikouch, Samir; Beerbaum, Philipp; Baumgartner, Helmut; Diller, Gerhard-Paul; ,
Abstract: Background: Electrical dyssynchrony and prolonged QRS duration are common in patients with repaired tetralogy of Fallot (ToF). It has been linked to increased risk of sudden cardiac death and right ventricular (RV) dysfunction. We investigated myocardial dyssynchrony using cardiac magnetic resonance imaging (CMR) and feature tracking analysis (FT) in this setting and compared it to myocardial deformation, conventional parameters of ventricular dysfunction and clinical parameters. Methods and results: Patients underwent standardized CMR investigations as part of a nationwide study. We prospectively assessed myocardial deformation and analysed regional wall motion abnormalities of the RV and the left ventricle (LV) using CMR-FT. The main measure of dyssynchrony was the maximal time difference (wall motion delay) of the regional strain as a parameter of mechanical biventricular dyssynchrony. In addition, clinical parameters and measures of cardiopulmonary exercise capacity were available. Overall 345 patients were included. Parameters of biventricular wall motion delay correlated significantly with global FT-strain parameters (p < 0.0001 for all imaging planes assessed). Furthermore, we found a significant correlation between circumferential RV motion delay and QRS duration (p = 0.006). Higher LV and RV wall motion delay parameters were also associated with lower peak oxygen consumption (p < 0.05) and a worse LV and RV ejection fraction (p < 0.02). Conclusions: Assessment of mechanical dyssynchrony is feasible using CMR-FT in ToF patients. Parameters of mechanical dyssynchrony correlate with electrical dyssynchrony, biventricular function and objective exercise capacity in this setting. Due to the weak degree of correlation, however, the clinical significance of these findings remains to be clarified by further studies.